2018
DOI: 10.3390/rs10040500
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Assessment of Hyperspectral Indicators for the Detection of Buried Archaeological Relics

Abstract: Hyperspectral images can highlight crop marks in vegetated areas, which may indicate the presence of underground buried structures, by exploiting the spectral information conveyed in reflected solar radiation. In recent years, different vegetation indices and several other image features have been used, with varying success, to improve the interpretation of remotely sensed images for archaeological research. However, it is difficult to assess the derived maps quantitatively and select the most meaningful one f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
(48 reference statements)
1
20
0
1
Order By: Relevance
“…At present archaeological crop mark identification relies largely on traditional observer‐directed manual approaches, which brings with it the issues of confirmation bias and the limitations of an entirely human based visible spectrum approach to image analysis. As semi‐automated approaches to analysis are explored, it will be vital to have data that can support discrimination between archaeological regions of crop stress independent of prior sources of bias (Bennett et al, ; Cerra et al, ; Traviglia, Cowley, & Lambers, ). Whilst the change detected in both the multispectral and RGB results from this study was partially defined by visual analysis, the separability found shows promise that as analytical techniques develop (including methods such as edge detection, unsupervised classification and object‐based image analysis), change regions may be automatically rather than manually classified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present archaeological crop mark identification relies largely on traditional observer‐directed manual approaches, which brings with it the issues of confirmation bias and the limitations of an entirely human based visible spectrum approach to image analysis. As semi‐automated approaches to analysis are explored, it will be vital to have data that can support discrimination between archaeological regions of crop stress independent of prior sources of bias (Bennett et al, ; Cerra et al, ; Traviglia, Cowley, & Lambers, ). Whilst the change detected in both the multispectral and RGB results from this study was partially defined by visual analysis, the separability found shows promise that as analytical techniques develop (including methods such as edge detection, unsupervised classification and object‐based image analysis), change regions may be automatically rather than manually classified.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have looked at how wider ranges of spectral information captured by both airborne and spaceborne multispectral sensors may be most effectively, and subjectively, exploited for archaeological prospection particularly in comparison to aerial photography (Agapiou et al, ; Bennett et al, ; Doneus et al, ; Traviglia, ; Verhoeven & Sevara, ). Different vegetation indices (VIs), mathematical combinations of observed wavelength bands, have been widely studied in the search for improved visual enhancements in processed images (Agapiou et al, ; Bennett et al, ; Bennett, Welham, Hill, & Ford, ; Cerra, Agapiou, Cavalli, & Sarris, ; Challis, Kincey, & Howard, ; De Guio, ; Traviglia, ; Verhoeven & Doneus, ). Over 150 VIs have been utilised across different studies (Bennett et al, ) although their comparative effectiveness for crop mark detection has been found to vary depending on observing conditions (Agapiou et al, ; Aqdus et al, ; Aqdus, Drummond, & Hanson, ; Bennett et al, ; Cerra et al, ; Challis et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such subjectivity must be avoided, and hyperspectral remote sensing is an optimal tool for this.A plethora of techniques, analyses and applications for hyperspectral remote sensing have been developed in the last few decades [3]. It has been used for the documentation of murals [4], detection of buried archaeological relics [5], and exploration of their geologic [6] or mineralogic composition. It has a number of advantages [7]: It is considered a safe detection technique because it is non-contact and non-destructive.…”
mentioning
confidence: 99%